Relationship Between Persuasive Communication with Student's Participation in Welfare Empowerment Program Sikapak Timur Village, Pariaman City. - Fitri Indah Sari; Irmawita Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
The background of this research is the low participation of learners in the PKK program in the East Attitude Village of Pariaman City. This is presumably due to the low persuasion communication of the instructor to the learning community in the PKK program. This study aims to see: 1) an overview of persuasive communication in the PKK program in East Attitude Village, Pariaman City, 2) a description of the participation of learners in making ginger powder in the PKK program at Attitudeak Timur Village, Pariaman City, 3) knowing the relationship between persuasive communication and the participation of learners in making ginger powder in the PKK program at Attitudeak Timur Village, Pariaman City.This study uses a quantitative approach, with the type of correlation which aims to determine the relationship of persuasion communication with the participation of learners in the PKK program in East Attitude Village, Pariaman City. The research population is 35 people and the sampling technique uses Stratified Random Sampling and taken as many as 70%, namely 25 people. Techniques in collecting data using questionnaires and data collection tools in the form of a list of statements. The data analysis technique uses the percentage formula and Rank Order.The results of the study found that: 1) The description of the persuasive communication of learners in the PKK program in the East Attitude Village of Pariaman City was categorized as low; 2) The description of the participation of learners in the PKK program in the East Attitude Village of Pariaman City is categorized as low, and; 3) There is a significant relationship between persuasion communication and the participation of learners in the PKK program in the East Attitude Village of Pariaman City. Furthermore, suggestions are expected for further researchers to examine new variables so that they can multiply and complete the variables to be studied further.Keywords: Persuasion Communication; Participation